2022
DOI: 10.1155/2022/6929776
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Experimental Investigations on the Sugarcane Cutting Mechanism and Effects of Influence Factors on the Cutting Quality of Small Sugarcane Harvesters under Vibration Excitations

Abstract: In order to study the sugarcane cutting mechanism and the effects of influence factors on the sugarcane cutting quality (SCQ) of small sugarcane harvesters in hilly areas, sugarcane cutting experiments and simulations were done through a self-developed sugarcane harvester experiment platform (SHEP) and the finite element analysis (FEA) method. The comprehensive cutting quality evaluating value (CCQEV) was calculated through the number of sugarcane cracks, the crack thickness, and the crack length to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Based on previous studies, it could be found that the physical morphological characteristics of stalk were very important for its mechanical properties. In order to measure the mechanical property of the stalk, the relationship between the mechanical properties and physical properties should be studied [16,17]. ese viewpoints could also be verified from this article.…”
Section: Mechanical Property Parameters Of Oil Peony Stalkmentioning
confidence: 78%
See 1 more Smart Citation
“…Based on previous studies, it could be found that the physical morphological characteristics of stalk were very important for its mechanical properties. In order to measure the mechanical property of the stalk, the relationship between the mechanical properties and physical properties should be studied [16,17]. ese viewpoints could also be verified from this article.…”
Section: Mechanical Property Parameters Of Oil Peony Stalkmentioning
confidence: 78%
“…e relationship between the breaking force of oil peony seed and related factor was established [15]. In addition to the parameters of the cutting equipment, the mechanical properties of the stalk were varied with the change of the stalk diameter, internode distance, weight, and moisture content [16,17]. Other engineering property parameters of oil peony stalk, for example, the chemical components of hemicellulose, cellulose, and lignin, were different with other crops, which was worth discussing.…”
Section: Introductionmentioning
confidence: 99%
“…According to Table 7, the output frequency corresponding to 20 Hz is 5.86 Hz close to 6 Hz, in the main excitation frequency band of sugarcane field roughness, 1–6 Hz. According to the LMS modal test result of the SHEP got previously by our research group, 26 the first natural frequency of the SHEP is 6.819 Hz which is between 6 Hz and 7 Hz. 5.86 Hz is close to the first natural frequency of the SHEP, 6.819 Hz.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, according to Figure 9, when the input frequency of the SSFE is 20 Hz, a wave crest of 26 the first natural frequency of the SHEP is 6.819 Hz which is between 6 Hz and 7 Hz. 5.86 Hz is close to the first natural frequency of the SHEP, 6.819 Hz.…”
Section: Analysis On the Ssfe Output Frequency Calibration Experiment...mentioning
confidence: 99%
See 1 more Smart Citation